Validation of the French version of the Pittsburgh Sleep Quality Index Addendum for posttraumatic stress disorder - Malik Ait-Aoudia; Pierre P. Levy; Eric Bui; Salvatore Insana; Capucine de Fouchier; Anne Germain; Louis Jehel (European Journal of Psychotraumatology, 2013)
Background: Sleep disturbances are one of the main complaints of patients with trauma-related disorders. The original Pittsburgh Sleep Quality Index Addendum for PTSD (PSQI-A) is self-report instrument developed to evaluate posttraumatic stress disorder (PTSD)-specific sleep disturbances in trauma-exposed individuals. However, to date, the PSQI-A has not yet been translated nor validated in French. Objective: The present study aims to: a) translate the PSQI-A into French, and b) examine its psychometric properties. Method: Seventy-three adult patients (mean age=40.3 [SD=15.0], 75% females) evaluated in a specialized psychotraumatology unit completed the French versions of the PSQI-A, Pittsburgh Sleep Quality Index (PSQI), Hospital Anxiety and Depression Scale (HADS), and Impact Event Scale-Revised (IES-R). Results: The French version of the PSQI-A showed satisfactory internal consistency, inter-item correlations, item correlations with the total score, convergent validity with PTSD and anxiety measures, and divergent validity with a depression measure. Conclusion: Our findings support the use of the French version of the PSQI-A for both clinical care and research. The French version of the PSQI-A is an important addition to the currently available instruments that can be used to examine trauma-related sleep disturbances among French-speaking individuals.